2014
DOI: 10.1371/journal.pone.0089577
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Dual-Specificity Phosphatase 5 Pseudogene 1 (DUSP5P1) in Tumor Cells

Abstract: Sequencing of individual clones from a newly established cDNA library from the chemoresistant Hodgkin's lymphoma cell line L-1236 led to the isolation of a cDNA clone corresponding to a short sequence from chromosome 1. Reverse transcriptase-polymerase chain reaction indicated high expression of this sequence in Hodgkin's lymphoma derived cell lines but not in normal blood cells. Further characterization of this sequence and the surrounding genomic DNA revealed that this sequence is part of a human endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…At 3 months, we identified two regions on chromosome 1 associated with decreased methylation of the DUSP5P1 pseudogene in the family of MAPK phosphatases. Studies suggest that this gene may act as a tumor suppressor in hematopoietic malignancies [45,46]. In the current study, we observed a decrease in methylation following the MBC2 intervention, which may indicate an upregulation of DUSP5P1 and tumor suppression.…”
Section: Discussionsupporting
confidence: 65%
“…At 3 months, we identified two regions on chromosome 1 associated with decreased methylation of the DUSP5P1 pseudogene in the family of MAPK phosphatases. Studies suggest that this gene may act as a tumor suppressor in hematopoietic malignancies [45,46]. In the current study, we observed a decrease in methylation following the MBC2 intervention, which may indicate an upregulation of DUSP5P1 and tumor suppression.…”
Section: Discussionsupporting
confidence: 65%
“…HL is a lympho-proliferative disease with known re-activation of HERV-like sequences (Lamprecht et al, 2010 ; Staege et al, 2014 ). The majority of HL patients can be cured today, but the toxicity of the used therapy regimes is high.…”
Section: Resultsmentioning
confidence: 99%
“…As an lncRNA, DUSP5P1 is a pseudogene of DUSP5. The DUSP5/ DUSP5P1 system could be responsible for regulation of BCL2L11 leading to the inhibition of apoptosis in HL cells (18). High expression of DUSP5P1 is identified in high-risk AML patients and is associated with poor prognosis in AML (14).…”
Section: Discussionmentioning
confidence: 99%